Strategi Peningkatan Motivasi Belajar Siswa di Sekolah Dasar - Abdul Fattah Nasution; Amelia Amelia; Soleh Parlindungan; Zuchairunnisa Zuchairunnisa (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This research aims to determine strategies for increasing student learning motivation at school. This research uses qualitative case study research. the ability of elementary school teachers to implement their strategies comprehensively and in depth. So that students have high motivation, several efforts need to be made by the teacher to generate that motivation. That is, good, correct and interesting learning media can be used. The aim of using learning media in the teaching and learning process is to arouse new interests and desires, generate motivation and stimulation of learning activities, and even have psychological influences on learning. Explaining the benefits or objectives of the lesson that students really feel will raise students' learning motivation. As has been stated, motivation is an impulse that causes someone to do something. With motivation there will be an urge to do something in relation to achieving goals.